Aerosol Jet Printing: Challenges and Advances in Aerosol Jet Printing of Regenerated Silk Fibroin Solutions (Adv. Mater. Interfaces 12/2020). Issue 12 (23rd June 2020) - Xiao, Yuhan; Kalaitzidou, Kyriaki; Yao, Donggang; Yeo, Woon‐Hong; Harris, Tequila A. L.
Abstract : Aerosol jet printing (AJP) of regenerated silk fibroin (RSF) solutions is challenging due to rheological and wetting effects and the delicate balance between solution preparation and material fabrication. In article number 1902005 by Tequila A. L. Harris and co‐workers methods for formulating RSF solutions and tuning process conditions to fabricate high‐quality RSF thin film using AJP, with limited defects e.g., gelation and overspray, relative to the focus ratio are discussed.